(untitled) (Journal of Educational Management, 2012)
The study sought to explore factors influencing the low representation of women in management positions in the University of Cape Coast. An exploratory qualitative research design was employed to undertake the study. Data was collected through interviews with forty-one workers in management positions and analysed using the N6 package for analyzing qualitative research. Generally, the respondents were of the view that women are not well represented in management positions. Notable reasons they gave included lack of requisite qualifications on the side of women and the University being gender sensitive. The problems women in management positions faced were stressful career workload and domestic/family responsibilities and these kept them from climbing the managerial ladder. The respondents were of the view that women needed more opportunities to excel and aspire for management positions. The situation can be improved if institutions formulate policies geared toward fast tracking women with leadership potentials.